Study on the dynamic load sharing characteristics of nutation face gear transmission - Wang Li; Yufeng Gao; Jingzi Zhang (Discover Applied Sciences)
Abstract The nutation face gear transmission is a type of power splitting, and the effects of system parameters such as stiffness and transmission error on load distribution are not yet well understood. The Load Tooth Contact Analysis (LTCA) technique was used to calculate the time-varying meshing stiffness of the conjugate face gear pair. A 22-degree-of-freedom bending-torsional-axial coupled dynamic model of the system was established considering parameters such as support stiffness, time-varying meshing stiffness, meshing error, and installation error. A test bench for nutation face gear transmission system was set up, and experimental results shown that the dynamic model of the nutation face gear system had an accuracy of 2.32%. Based on the solution of the dynamic meshing force of the conjugate face gear pairs, the dynamic load sharing coefficient of the nutation face gear transmission system was defined. Through simulation calculations, the effects of support stiffness, comprehensive meshing error, and torsional stiffness of input shaft on the dynamic load characteristics of the system were analyzed. The research results indicate that the radial support stiffness of each face gear and the coupling stiffness between the oblique axis segment of the input shaft has the greatest impact on the load sharing coefficient. Reducing the radial support stiffness of the left branch, increasing the radial support stiffness of the right branch, and increasing the coupling stiffness between the oblique axis segment of the input shaft can improve the system's load-sharing performance by 76%. The asymmetry of the comprehensive meshing error parameters in the two power transmission branches can increase the system's load-sharing coefficient up to 1.8. These findings provide an important basis for the structural and stiffness parameter design of nutating face gear transmissions.